Solve the following equations: $\dfrac{{xy}}{{ay + bx}} = c,\dfrac{{xz}}{{az + cx}} = b,\dfrac{{yz}}{{bz + cy}} = a$.
Answer
Verified
512.1k+ views
Hint- Here, we will simplify the given equations in order to evaluate the values of $x$ ,$y$ and $z$.
Given equations are $\dfrac{{xy}}{{ay + bx}} = c,\dfrac{{xz}}{{az + cx}} = b,\dfrac{{yz}}{{bz + cy}} = a$
The above equations can be re-written as
$
\dfrac{{ay + bx}}{{xy}} = \dfrac{1}{c},\dfrac{{az + cx}}{{xz}} = \dfrac{1}{b},\dfrac{{bz + cy}}{{yz}} = \dfrac{1}{a} \Rightarrow \dfrac{{ay}}{{xy}} + \dfrac{{bx}}{{xy}} = \dfrac{1}{c},\dfrac{{az}}{{xz}} + \dfrac{{cx}}{{xz}} = \dfrac{1}{b},\dfrac{{bz}}{{yz}} + \dfrac{{cy}}{{yz}} = \dfrac{1}{a} \\
\Rightarrow \dfrac{a}{x} + \dfrac{b}{y} = \dfrac{1}{c}{\text{ }} \to {\text{(1) }},\dfrac{a}{x} + \dfrac{c}{z} = \dfrac{1}{b}{\text{ }} \to {\text{(2) }},\dfrac{b}{y} + \dfrac{c}{z} = \dfrac{1}{a}{\text{ }} \to {\text{(3)}} \\
\\
$
Now adding all the above three equations, we have
$
\Rightarrow \dfrac{a}{x} + \dfrac{b}{y} + \dfrac{a}{x} + \dfrac{c}{z} + \dfrac{b}{y} + \dfrac{c}{z} = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow 2\left[ {\dfrac{a}{x} + \dfrac{b}{y} + \dfrac{c}{z}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a}{\text{ }} \to {\text{(4)}} \\
\Rightarrow 2\left[ {\dfrac{a}{x} + \left( {\dfrac{b}{y} + \dfrac{c}{z}} \right)} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \\
$
Since, we have already shown that $\dfrac{b}{y} + \dfrac{c}{z} = \dfrac{1}{a}$ according to equation (3)
$
\therefore {\text{ }}2\left[ {\dfrac{a}{x} + \dfrac{1}{a}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{{2a}}{x} + \dfrac{2}{a} = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{{2a}}{x} + \dfrac{1}{a} = \dfrac{1}{c} + \dfrac{1}{b} \\
\Rightarrow \dfrac{{2a}}{x} = \dfrac{1}{c} + \dfrac{1}{b} - \dfrac{1}{a} \Rightarrow \dfrac{{2a}}{x} = \dfrac{{ab + ac - bc}}{{abc}} \Rightarrow \dfrac{x}{{2a}} = \dfrac{{abc}}{{ab + ac - bc}} \\
\Rightarrow x = \dfrac{{2{a^2}bc}}{{ab + ac - bc}} \\
$
Considering equation (4) again, we have
$ \Rightarrow 2\left[ {\dfrac{a}{x} + \dfrac{b}{y} + \dfrac{c}{z}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a}{\text{ }} \Rightarrow 2\left[ {\dfrac{b}{y} + \left( {\dfrac{a}{x} + \dfrac{c}{z}} \right)} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a}{\text{ }}$
Since, we have already shown that $\dfrac{a}{x} + \dfrac{c}{z} = \dfrac{1}{b}$ according to equation (2)
$
\therefore {\text{ }}2\left[ {\dfrac{b}{y} + \dfrac{1}{b}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{{2b}}{y} + \dfrac{2}{b} = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{{2b}}{y} + \dfrac{1}{b} = \dfrac{1}{c} + \dfrac{1}{a} \\
\Rightarrow \dfrac{{2b}}{y} = \dfrac{1}{c} + \dfrac{1}{a} - \dfrac{1}{b} \Rightarrow \dfrac{{2b}}{y} = \dfrac{{ab + bc - ac}}{{abc}} \Rightarrow \dfrac{y}{{2b}} = \dfrac{{abc}}{{ab + bc - ac}} \\
\Rightarrow y = \dfrac{{2a{b^2}c}}{{ab + bc - ac}} \\
$
Considering equation (4) again, we have
\[ \Rightarrow 2\left[ {\dfrac{a}{x} + \dfrac{b}{y} + \dfrac{c}{z}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a}{\text{ }} \Rightarrow 2\left[ {\left( {\dfrac{a}{x} + \dfrac{b}{y}} \right) + \dfrac{c}{z}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a}{\text{ }}\]
Since, we have already shown that $\dfrac{a}{x} + \dfrac{b}{y} = \dfrac{1}{c}$ according to equation (1)
$
\therefore {\text{ }}2\left[ {\dfrac{1}{c} + \dfrac{c}{z}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{2}{c} + \dfrac{{2c}}{z} + = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{{2c}}{z} + \dfrac{1}{c} = \dfrac{1}{b} + \dfrac{1}{a} \\
\Rightarrow \dfrac{{2c}}{z} = \dfrac{1}{a} + \dfrac{1}{b} - \dfrac{1}{c} \Rightarrow \dfrac{{2c}}{z} = \dfrac{{bc + ac - ab}}{{abc}} \Rightarrow \dfrac{z}{{2c}} = \dfrac{{abc}}{{bc + ac - ab}} \\
\Rightarrow z = \dfrac{{2ab{c^2}}}{{bc + ac - ab}} \\
$
Therefore, after solving the given equations we get
$x = \dfrac{{2{a^2}bc}}{{ab + ac - bc}}$, $y = \dfrac{{2a{b^2}c}}{{ab + bc - ac}}$ and $z = \dfrac{{2ab{c^2}}}{{bc + ac - ab}}$.
Note- In this particular problem, equations (1), (2) and (3) are used in equation (4) one by one in order to eliminate the other two variables and solve for the remaining one variable only.
Given equations are $\dfrac{{xy}}{{ay + bx}} = c,\dfrac{{xz}}{{az + cx}} = b,\dfrac{{yz}}{{bz + cy}} = a$
The above equations can be re-written as
$
\dfrac{{ay + bx}}{{xy}} = \dfrac{1}{c},\dfrac{{az + cx}}{{xz}} = \dfrac{1}{b},\dfrac{{bz + cy}}{{yz}} = \dfrac{1}{a} \Rightarrow \dfrac{{ay}}{{xy}} + \dfrac{{bx}}{{xy}} = \dfrac{1}{c},\dfrac{{az}}{{xz}} + \dfrac{{cx}}{{xz}} = \dfrac{1}{b},\dfrac{{bz}}{{yz}} + \dfrac{{cy}}{{yz}} = \dfrac{1}{a} \\
\Rightarrow \dfrac{a}{x} + \dfrac{b}{y} = \dfrac{1}{c}{\text{ }} \to {\text{(1) }},\dfrac{a}{x} + \dfrac{c}{z} = \dfrac{1}{b}{\text{ }} \to {\text{(2) }},\dfrac{b}{y} + \dfrac{c}{z} = \dfrac{1}{a}{\text{ }} \to {\text{(3)}} \\
\\
$
Now adding all the above three equations, we have
$
\Rightarrow \dfrac{a}{x} + \dfrac{b}{y} + \dfrac{a}{x} + \dfrac{c}{z} + \dfrac{b}{y} + \dfrac{c}{z} = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow 2\left[ {\dfrac{a}{x} + \dfrac{b}{y} + \dfrac{c}{z}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a}{\text{ }} \to {\text{(4)}} \\
\Rightarrow 2\left[ {\dfrac{a}{x} + \left( {\dfrac{b}{y} + \dfrac{c}{z}} \right)} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \\
$
Since, we have already shown that $\dfrac{b}{y} + \dfrac{c}{z} = \dfrac{1}{a}$ according to equation (3)
$
\therefore {\text{ }}2\left[ {\dfrac{a}{x} + \dfrac{1}{a}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{{2a}}{x} + \dfrac{2}{a} = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{{2a}}{x} + \dfrac{1}{a} = \dfrac{1}{c} + \dfrac{1}{b} \\
\Rightarrow \dfrac{{2a}}{x} = \dfrac{1}{c} + \dfrac{1}{b} - \dfrac{1}{a} \Rightarrow \dfrac{{2a}}{x} = \dfrac{{ab + ac - bc}}{{abc}} \Rightarrow \dfrac{x}{{2a}} = \dfrac{{abc}}{{ab + ac - bc}} \\
\Rightarrow x = \dfrac{{2{a^2}bc}}{{ab + ac - bc}} \\
$
Considering equation (4) again, we have
$ \Rightarrow 2\left[ {\dfrac{a}{x} + \dfrac{b}{y} + \dfrac{c}{z}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a}{\text{ }} \Rightarrow 2\left[ {\dfrac{b}{y} + \left( {\dfrac{a}{x} + \dfrac{c}{z}} \right)} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a}{\text{ }}$
Since, we have already shown that $\dfrac{a}{x} + \dfrac{c}{z} = \dfrac{1}{b}$ according to equation (2)
$
\therefore {\text{ }}2\left[ {\dfrac{b}{y} + \dfrac{1}{b}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{{2b}}{y} + \dfrac{2}{b} = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{{2b}}{y} + \dfrac{1}{b} = \dfrac{1}{c} + \dfrac{1}{a} \\
\Rightarrow \dfrac{{2b}}{y} = \dfrac{1}{c} + \dfrac{1}{a} - \dfrac{1}{b} \Rightarrow \dfrac{{2b}}{y} = \dfrac{{ab + bc - ac}}{{abc}} \Rightarrow \dfrac{y}{{2b}} = \dfrac{{abc}}{{ab + bc - ac}} \\
\Rightarrow y = \dfrac{{2a{b^2}c}}{{ab + bc - ac}} \\
$
Considering equation (4) again, we have
\[ \Rightarrow 2\left[ {\dfrac{a}{x} + \dfrac{b}{y} + \dfrac{c}{z}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a}{\text{ }} \Rightarrow 2\left[ {\left( {\dfrac{a}{x} + \dfrac{b}{y}} \right) + \dfrac{c}{z}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a}{\text{ }}\]
Since, we have already shown that $\dfrac{a}{x} + \dfrac{b}{y} = \dfrac{1}{c}$ according to equation (1)
$
\therefore {\text{ }}2\left[ {\dfrac{1}{c} + \dfrac{c}{z}} \right] = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{2}{c} + \dfrac{{2c}}{z} + = \dfrac{1}{c} + \dfrac{1}{b} + \dfrac{1}{a} \Rightarrow \dfrac{{2c}}{z} + \dfrac{1}{c} = \dfrac{1}{b} + \dfrac{1}{a} \\
\Rightarrow \dfrac{{2c}}{z} = \dfrac{1}{a} + \dfrac{1}{b} - \dfrac{1}{c} \Rightarrow \dfrac{{2c}}{z} = \dfrac{{bc + ac - ab}}{{abc}} \Rightarrow \dfrac{z}{{2c}} = \dfrac{{abc}}{{bc + ac - ab}} \\
\Rightarrow z = \dfrac{{2ab{c^2}}}{{bc + ac - ab}} \\
$
Therefore, after solving the given equations we get
$x = \dfrac{{2{a^2}bc}}{{ab + ac - bc}}$, $y = \dfrac{{2a{b^2}c}}{{ab + bc - ac}}$ and $z = \dfrac{{2ab{c^2}}}{{bc + ac - ab}}$.
Note- In this particular problem, equations (1), (2) and (3) are used in equation (4) one by one in order to eliminate the other two variables and solve for the remaining one variable only.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
When people say No pun intended what does that mea class 8 english CBSE
In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE
How many ounces are in 500 mL class 8 maths CBSE
Which king started the organization of the Kumbh fair class 8 social science CBSE
What is BLO What is the full form of BLO class 8 social science CBSE
Advantages and disadvantages of science